Reduction of Aggressive Behavior Levels in Adolescent Adolescents with Emotional Regulation Therapy - Endang Mei Yunalia; Idola Perdana Sulistyoning Suharto (Universitas Muhammadiyah Semarang, 2020)
Aggressive behavior is a behavior disorder especially if it occurs repeatedly and persists for at least 6 months. Aggressive behavior occurs because adolescent express negative emotions in an inappropriate way. The solution to help adolescent to be able to express emotions appropriately is with emotion regulation therapy. The purpose of this study was to determine the effectiveness of emotional regulation therapy on the level of aggressive behavior in young men. This research is a Quasy experimental study using one group pre-post test design with control design. The population in this study was all young men with